Islam Dibawa Masuk oleh Orang Nusantara: Dari Data Terserak Buzurgh Al-Ramahurmuzi, 'Ajaibul Hind: Kisah-Kisah Ajaib di Daratan dan Lautan Hindi - Masudi, Idris (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2020)
Studies of the archipelago (Nusantara) on the notes of foreign travelers written in the 9th and 10th of centuries are still quite rare. Indeed, there have been several studies on the notes of travelers such as Ma Huan (China), Tome Pires (Portuguese), Ibn Bathuthah (Arabic), and some others. But, these studies revolve around the notes of travelers after the 10th of century. Meanwhile, notes of travelers who came to the archipelago (Nusantara) in the century before 10 AD have not got serious attention yet. This book is a travel note's report which captures various activities in India, China and Southeast Asia. This book also contains a history about how Islam met in the Sarandib area. There are many interpretations of sarandib accurate location today. The findings of Keram Kevonian in his research on the names of regions in the Indian Ocean region using Armenian language sources stated that Sarandib means Swarnadipa which was no other than Sumatra.